Case Precedent in Qing China: Rethinking Traditional Case Law - Wang, Zhiqiang (Columbia Journal of Asian Law, 2005)
As part of the current effort to promote legal reform in China, the Chinese academic community has turned its attention to the function of case rulings and the role of judges. Over the past decade, members of domestic academia have discussed the implications of establishing a case law system in China. Under the current legal model, while decided cases play an important role in daily judicial administration as persuasive authority-especially those pronouncements by such higher courts as the Supreme People’s Court-these cases have yet to be recognized formally as a source of law. Inspired by this topic of practical concern, a number of Chinese legal historians have engaged in fierce debates about the nature of ancient China’s case law system. Some historians have argued that imperial China had a long history of implementing case law and, accordingly, they have proposed a revival of that tradition in modem society. Others have denied the universal existence of such a system in Chinese history, and still others have warned against possible misunderstandings arising from garbled usage of Western terminology without further exploration and detailed comparison.